Association of Abdominal Incision Length With Gastrointestinal Function Recovery Post-operatively: A Multicenter Registry System-Based Retrospective Cohort Study - Song, Jianning; Yang, Yingchi; Guan, Wenxian; Jin, Gang; Yang, Yinmo; Chen, Lin; Wan, Yong; Li, Leping; He, Qingsi; Zhang, Wei; Zhu, Weiming; Chen, Lei; et al. (Frontiers in Surgery, 2021)
Objective: The influence of abdominal incision length on gastrointestinal function recovery postoperatively was evaluated. Background: Gut motility recovers more quickly after minimally invasive laparoscopic surgery than after traditional open surgery; however, whether the minimal abdominal incision contributes to faster gut motility recovery is controversial and lacks solid clinical evidence. Methods: A registry-based secondary cohort analysis was conducted to evaluate the association between abdominal incision length and gut motility recovery postoperatively based on a multicenter, prospective, observational study of prolonged postoperative ileus (PPOI) incidence and risk factors in patients with major abdominal surgery. The incision length, in centimeters, was the exposure. The primary outcome measures were PPOI incidence and its association with incision length. The secondary outcome included days to first passage of flatus and days to first passage of stool. Results: In all, 1840 patients, including 287 (15.7%) with PPOI, were recruited. The PPOI incidence was 17.6% and 13.3% in long-incision (>18 cm) and short-incision patients (≤18 cm), respectively. The incidence of PPOI increased by 1.1% (1.0–1.1) by each centimeter increment of incision length after adjusting for confounding factors. Compared with the short-incision patients, the long-incision patients had prolonged passage of stool (4.46 days vs. 4.95 days p<0.001). Each centimeter increment of incision length contributed to a 2% increased risk of delay in the first bowel movement (HR 0.980 (0.967, 0.994)). Conclusions: A long abdominal incision length independently contributed to prolonged gut function recovery postoperatively, mainly by delaying the time to first bowel movement but not influencing the time to first passage of flatus.